Dried Blood Spot Sampling of Landlocked Arctic Char (Salvelinus alpinus) for Estimating Mercury Exposure and Stable Carbon Isotope Fingerprinting of Essential Amino Acids. (22nd March 2020) - Barst, Benjamin D.; Wooller, Matthew J.; O'Brien, Diane M.; Santa‐Rios, Andrea; Basu, Niladri; Köck, Günter; Johnson, Jessica J.; Muir, Derek C.G.
Abstract: Dried blood spots (DBS), created by applying and drying a whole blood sample onto filter paper, provide a simple and minimally invasive procedure for collecting, transporting, and storing blood. Because DBS are ideal for use in field and resource‐limited settings, we aimed to develop a simple and accurate DBS‐based approach for assessing mercury (Hg) exposure and dietary carbon sources for landlocked Arctic char, a sentinel fish species in the Arctic. We collected liquid whole blood (from the caudal vein), muscle, liver, and brains of Arctic char ( n = 36) from 8 lakes spanning a Hg gradient in the Canadian High Arctic. We measured total Hg concentrations ([THg]) of field‐prepared DBS and Arctic char tissues. Across a considerable range, [THg] of DBS (0.04–3.38 μg/g wet wt) were highly correlated with [THg] of all tissues ( r 2 range = 0.928–0.996). We also analyzed the compound‐specific carbon isotope ratios (expressed as δ 13 C values) of essential amino acids (EAAs) isolated from DBS, liquid whole blood, and muscle. The δ 13 C values of 5 EAAs (δ 13 CEAAs ; isoleucine [Ile], leucine [Leu], phenylalanine [Phe], valine [Val], and threonine [Thr]) from DBS were highly correlated with δ 13 CEAAs of liquid whole blood ( r 2 range = 0.693–0.895) and muscle ( r 2 range = 0.642–0.881). The patterns of δ 13 CEAAs of landlocked Arctic char were remarkably consistent across sample types and indicate that EAAs are most likely of algal origin. Because a small volume of blood ( 50 µL) dried on filter paper can be used to determine Hg exposure levels of various tissues and to fingerprint carbon sources, DBS sampling may decrease the burdens of research and may be developed as a nonlethal sampling technique. Environ Toxicol Chem 2020;39:893–903. © 2020 SETAC